A BOUNDARY PROBLEM OF THE THIRD AND FOURTH ORDERS AS A PRODUCT OF BOUNDARY PROBLEMS OF THE SECOND ORDER - Georgievska, Slobodanka S. (Matematichki Bilten, 1995)
Conditions when a boundary problem of the third and fourth orders has as a solution a product of the solutions of boundary problems of the second order in the case of general homogeneous boundary conditions have been obtained in this paper.